Prospecting Plant Extracts and Bioactive Molecules with Antimicrobial Activity in Brazilian Biomes: A Review - José Carlos Eloi de Queiroz; José Roberto S. A. Leite; Andreanne Gomes Vasconcelos (Antibiotics, 2023)
Antimicrobial resistance is currently one of the greatest threats to global health, food security, and development. In this aspect, medicinal plants have been studied to support the development of viable alternatives to prevent and treat infectious diseases. This study aimed to perform a review of the literature comprising the antimicrobial activity of vegetable species from Brazilian biomes. We selected 67 original scientific publications about extracts, fractions, or isolated molecules from plants in the Brazilian biomes, published between 2016 and 2020 in Pubmed, ScienceDirect, and Scielo. Data demonstrated that 98 plant species, especially collected in the Cerrado, Atlantic Forest, and Caatinga biomes, were tested against 40 fungi and 78 bacterial strains. Bioactive fractions of Eucalyptus globulus methanolic stump wood extract were active against Candida albicans and C. tropicalis (MIC 2.50 µg/mL). The catechin purified from Banisteriopsis argyrophylla leaves had activity against C. glabrata (MIC 2.83 µg/mL) and ethanolic extract obtained from Caryocar coriaceum bark and fruit pulp exhibited MIC of 4.1 µg/mL on Microsporum canis. For bacteria, compounds isolated from the dichloromethane extract of Peritassa campestris, lectin extracted from a saline extract of Portulaca elatior and essential oils of Myrciaria pilosa exhibited significant effect against Bacillus megaterium (MIC 0.78 µg/mL), Pseudomonas aeruginosa (MIC 4.06 µg/mL) and Staphylococcus aureus strains (MIC 5.0 µg/mL), respectively. The findings support the antimicrobial and bioeconomic potential of plants from Brazilian biodiversity and their promising health applications.